Acute acalculous cholecystitis of an intrahepatic gallbladder causing Mirizzi's syndrome. (13th April 2018) - Falk, Vanessa; Low, Gavin; Bigam, David; Sandha, Gurpal
Abstract : We present the case of a young female with symptoms of biliary colic and a biochemical profile consistent with biliary obstruction. Imaging was suspicious for Mirizzi's syndrome. Intraoperatively, the patient was found to have a complete intrahepatic gallbladder causing common hepatic duct compression with final pathology confirming acute cholecystitis. We review the embryological development of the gallbladder as well as clinical presentation of Mirizzi's syndrome. Special consideration for clinical workup and surgical management is discussed.